Drought safety levels assessment in Uzbekistan part of the Khorezm oasis by geospatial methods - Matchanov, Muzaffar; Mudarra, Matías; Nigmatov, Askar; Boymurodov, Rifat; Jumabayev, Ruslan; Hakimi, Ali; Matchanov, Otabek (Geodesy and Cartography, 2025)
The issue of drought has emerged as a significant challenge in the Khorezm oasis over recent decades. Furthermore, the construction of the Kushtepa canal in Afghanistan is expected to exacerbate the impact of drought in the region. It is of the utmost importance to evaluate the resilience of the oasis to drought in order to ensure effective planning and mitigation strategies. This study employed geospatial data, including the normalized difference of vegetation index (NDVI), land surface temperature (LST), normalized difference of moisture index (NDMI), soil brightness, groundwater table, digital elevation model (DEM), and distance to Amudarya river, derived from Landsat 5 TM, and Landsat 8 OLI/TIRS data (2000–2023). A weighted overlay analysis was employed to identify the most influential factors, which were found to be distance from the river, canal density, soil brightness, LST, and groundwater table. The findings indicate that 3746 km2 of the oasis is safe, while 4644.32 km2, 5563.77 km2, 5486.17 km2, 7832.64 km2 are classified as dangerous, mid dangerous, high dangerous, and extreme dangerous, respectively. It is recommended that agricultural use be prioritised in areas deemed safe, that construction be restricted, and that population migration from high-risk regions to safer areas be facilitated.